Epidemiological profile of gestational syphilis in a Regional Department of the state of São Paulo: incidence pattern and epidemiological characteristics from 2010 to 2021 (Research, Society and Development, 2022)
Syphilis is an infectious disease that can be transmitted sexually and vertically during pregnancy. With regard to the etiological agent, Treponema pallidum, it can affect several systems and organs. In addition, cases of Gestational Syphilis (GS) are recognized as a worldwide health problem. It is necessary to emphasize the importance of adopting strategies for the effectiveness of prenatal care provided and the focus on early diagnosis and consequent treatment of GS. Therefore, the epidemiological profile of cases of gestational syphilis in the cities that make up the Regional Department of Health XI was analyzed. From 2010 to 2021, the profile of Gestational Syphilis was carried out for the 45 municipalities, through calculations of the incidence rate of gestational syphilis in each year divided by the number of new confirmed cases per thousand live births for each municipality. Results show that the frequency of syphilis in these pregnant women showed an increasing trend. Socio-epidemiologically, we had a predominance of young women, with low education and in the diagnostic aspect, a prevalence of latent OS with a higher level of reagent tests in the period of the first trimester. Finally, this study will bring new epidemiological perspectives and thus facilitate the establishment of new strategies to reduce the number of cases of this disease. That said, the ecological assessment of this disease in pregnant women supports public health and the dissemination of knowledge to society.